A Morphological Analysis of Derivational Affixes in the Video of Barack Obama’s Speech - Neng Widi Khaerunisa; kheryadi kheryadi (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
This research analyzes the derivational affixes found in the video of Barack Obama's speech about education in 2016. This research was to find out the types of derivational affixes and to know the number of derivational affixes including prefixes and suffixes found in the video of Barack Obama's speech about education in 2016. This research used the descriptive qualitative method. The instruments used in this research were observation and documentation. The research finding of the last result showed that the total data of prefixes are 16 data, it consists of prefix ac-, re-, im-, pre- (1), in- (2), a- (2), un- (3). Meanwhile, the total data of suffixes are 47 data, they consist of suffix -ion (3), -ful (3), -ice (1), -ly (10), -ity (3), -ment (5), -ition (1), -ation (2), -ize (2), -y (3), -able (3), -al (1), -ial (1), -ible (1), -hood (1), -ance (1), -ic (1), -ive (1), -ness (1). Moreover, there are two types of derivational affixes are used in the video of Barack Obama's speech about education in 2016, they are class-changing derivational and class-maintaining derivational. The researcher hopes that the students are suggested to learn the use of derivational affixes. By learning the affixes, the students can improve their knowledge of new vocabularies. By knowing the roots, the readers can build the word by themselves.